ORALIDAD EN LOS PROCESOS DE LECTURA Y ESCRITURA - Martha Cecilia Ramos Beltrán; Angela Saturia Rojas Riveros (LÍNEA IMAGINARIA, 2025)
In a world of rapid change and unstoppable technological advances, it is necessary to establish transformations related to the ways of introducing children to reading and writing processes that respond to the current challenges of pedagogical practices. Therefore, it is necessary to discuss the impact that oral communication has on these processes. Recognizing that verbal communication influences the learning of reading and writing processes, it constitutes an essential skill in both the emotional and cognitive development of human beings, associated with linguistic competencies, which leads to a deeper study of strategies that strengthen its development. In this sense, this article aims to establish a reference framework that allows us to characterize relevant and innovative practice models for the development of oral language that contribute to strengthening these processes. The purpose of this article is to discuss the characteristics of the development of oral expression, so that they constitute the fundamental basis of learning. The purpose of this essay is to reflect on the need to strengthen oral communication in children to enhance the cognitive, social, and cultural processes that underpin the learning process and ensure literacy.